Eine Karte der hygrothermischen Klimatypen von Europa - Lauer, Wilhelm; Frankenberg, Peter (ERDKUNDE, 1986)
Within the framework of a project for the classification of the earth's climates, a Map of Hygrothermic Climatic Types of Europe is presented. While the basic idea of an ecological classification of climates is adhered to, the map represents a refinement of the methods developed by the authors for the Mexican Highlands and Africa. As basic factors for all terrestrial life, radiation-, heat and water-budget must serve as classificatory dimensions of the climates. In a solar-climatological sense the climatic zones are subdivided into Subtropics (B), Midlatitudes (C) and Polar Regions (D). Within these climatic zones the climatic regions (climatic types) are delimited by isothermomenes and isohygromenes according to the length of the thermic and hygric vegetation period. All months with an average mean temperature of >10°C are defined as the thermic vegetation period. The length of the humid season is considered as the hygric vegetation period. A month is called atmospherically humid, if precipitation (N) equals or exceeds the calculated optimal landscape evapotranspiration (oLV). The term oLV signifies that amount of evapotranspiration which allows a maximal biomass production of the actual vegetation. From the calculated ratesof the evaporation from open water surfaces (pV) the monthly rates of oLV are derived by conversion factors (UF), which allow for the seasonally variating aspects of the different natural and cultural vegetation units. Beside atmospherically humid, “edaphically humid months are classified, in which the vegetation can compensate precipitation deficiencies by using stored soil water. For fallow months and months with snow cover gliding conversion factors resp. absolute values, both based on thermic criteria, serve to calculate a. potential fallow evaporation (pBV) resp. a potential snow evaporation (pSV).